HUBUNGAN ANTARA BEBAN KERJA DENGAN STRES KERJA DITINJAU DARI WORKSHIFTPADA ATC DI KANTOR AIRNAV SURABAYA - Galuh Ratna Bidari; A.J. Tjahjoanggoro; Listyo Yuwanto (Perpustakaan Universitas Surabaya, 2018)
ATC is one of the professions that have pressure in the physical and psychological aspects where the profession is susceptible to be a one of the sources stress. Job stress with a mild or high level, depending on the factors that become a source of stress (stressor). Workshift is other things that can affect the level of work stress. The number of subjects in this study as many as 49 people ATC with a total population of 81 people. This study aims to determine the relationship between workload and work stress in terms of workshifts on ATC using quantitative research methods. The result of this research is to receive H0 meaning that there is no relation between work load with work stress either on morning shift (r = 0122), day shift (r = -0.097) and night shift (r = -0.180). There are other factors that can be a source of stress (stressor) in addition to the workload of social relationships, management style, organizational conditions, work family conflict, personality type and job experience.